Cefoxitin, a Semisynthetic Cephamycin Antibiotic: Susceptibility Studies - Wallick, Hyman (1974)
Cefoxitin, 3-carbamoyloxymethyl-7-α-methoxy-7-[2-(2-thienyl)acetamido]-3-cephem-4- carboxylic acid, is a new semisynthetic cephamycin with broad antibacterial activity. It is highly active against gram-negative microorganisms including indole-positive Proteus and Serratia strains, which are ordinarily reistant to the cephalosporins. Cefoxitin is also highly active against many strains of Escherichia coli and Proteus mirabilis which are resistant to the cephalosporins. Furthermore, E. coli and Klebsiella strains which are susceptible to the cephalosporins are generally more susceptible to the cephamycin analog. The susceptibility of the gram-positive bacteria falls well within the effective range of the antibiotic for gram-negative organisms, but cefoxitin is less active than cephalothin or cephaloridine. As is the case with the cephalosporins, strains of Pseudomonas and group D streptococci are resistant to cefoxitin. Changes in pH, inoculum density, and growth medium have no significant effect on the activity of the antibiotic.